LAYANAN INFORMASI KARIER TEHNIK e-LEARNING MEMANTAPKAN PILIHAN KARIER SISWA KELAS X SMA - Ismadi Ismadi (Counsellia: Jurnal Bimbingan dan Konseling, 2014)
Seeing a new era in education, namely the introduction of educationalreforms that are closely related to the information systems needed in thedevelopment of education, then developed a career information service with e-Learning techniques aimed at 1) see the condition of the implementation of careerservices at SMAN 1 Ponorogo 2) find the implementation models careerinformation with e-Learning techniques 3) look at the effectiveness of careerinformation service with e-Learning techniques. Research and development is amethod used to produce a particular product, and test the effectiveness of theproduct. Results and conclusions of this study were 1) to know the implementationof career information service in SMAN 1 Ponorogo 2) the discovery of careerinformation service model with e-Learning techniques for establishing thedirection select careers class X 3) determine the effectiveness of careerinformation service model with techniques of e-Learning to select a careerdirection establish class X.